Nalar Politik Kewilayaan Kesultanan Tidore: Studi Transmigrasi Lokal dan Makna Realitas Sosial Orang Tidore di Halmahera - Bustamin Wahid; Uswatul Mardliyah; La Basri; Siti Nurul Nikmatul Ula (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
This article aims to examine and analyse the political reasoning of the Tidore Sultanate regarding local transmigration policies and to explore the new social reality of the Tidore people in Halmahera, who have demonstrated resilience in the face of socio-political change, from the perspective of social capital. The methodology employed is qualitative descriptive, utilising a historical approach. Data were collected through observation, interviews, and document analysis, and subsequently analysed according to predefined criteria. The findings of this study reveal some interesting phenomena. Firstly, the political rationale of the Tidore Sultanate centred on the arguments put forward by Sultan Zainal Abidin. There were four key arguments put forward by the sultanate regarding the transmigration programme: (a) the mobilisation of Islamic forces from Tidore to the Halmahera lowlands (Islamisation); (b) the prevention of Christianisation among the Sangir and Tobelo-Galela tribes in the North Oba region; (c) anticipation of settlement migration from Java to areas outside Java; (d) local migration to Halmahera as part of a political security and defence strategy in the run-up to the struggle for West Irian. Secondly, the new social reality of the Tidore people in Halmahera has revitalised social modalities—marong, galasi and galoli—in search of new social meaning. These mechanisms are underpinned by the community’s social compliance and cultural spirituality